(untitled) (Fiep Bulletin - online, 2017)
Introduction: The knowledge of the functions that interact in the process of training and development in sportspreparation leads to reflection on the search for different procedures and methods for the current interest in the world of sport,especially in soccer. Objective: To evaluate the technical level of the athletes of the basic categories of a professional club of thecity of Patos - PB. Materials and Methods: Twenty young soccer players from the Sub-categories of the professional club ofPatos-PB were evaluated. The study was developed through the evaluation and technical skills of the soccer being necessary todo this to evaluate the dribble, the pass, the kick of the athletes, to measure the domain, medium and long pass or launch, tomeasure the domain, to dribble and to pass, to measure the domain , Dribbling and kicking, measuring the field, conducting andlong pass or throwing, measuring the field and kicking or finishing and, therefore, to evaluate the technical level of the athletes ofthe base categories of a professional club of the city of Patos - PB. The present study is a cross-sectional, descriptive study andafter the tests were performed the athletes were duly scored for evaluation by means of classification with their data analyzedthrough the descriptive statistics. Results: The analysis of the present study was to perform a test series where the data for all thetechnical level tests are specific for field soccer. The age of the patients was 13 to 15 years. The results show that 35% ofadolescents are considered to be WEAK, 50% considered REGULAR and 15% of adolescents considered being GOOD.CONCLUSION: We can say that with tests aimed at positioning the results would be different, but as they were done in generalthe results of the research are presented above where the athletes show that they can improve in several abilities including thosethat did well.